2019
DOI: 10.1016/j.ausmj.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Emerging Research Topics for Brand Personality: A Bibliometric Analysis

Abstract: This article details an eclectic bibliometric method to study brand personality, identifying theoretical buildings and possible emerging research topics across marketing science fields. A mix of diverse bibliometric software and multiple correspondence analyses related to the topic supports considerations of four methodological phases, in particular: (1) research overview, (2) authors, (3) semantics, and (4) models. The bibliometric findings offer a catalog of BP research approaches. A comparison of research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…It comprises five dimensions, namely, sincerity, excitement, competence, sophistication and ruggedness. Although this scale, as noted above, is the most widespread means to measure brand personality (Kumar, 2018), certain authors suggest that its characteristics and dimensions vary from sector to sector (Davies et al, 2018;Ferrandi et al, 2000;Geuens et al, 2009;G omez, 2010;Lara-Rodríguez et al, 2019;Supphellen and Grønhaug, 2003). Of these, sincerity, competence, excitement and sophistication are the dimensions most widely identified when brand personality is applied in different sectors (Davies et al, 2018).…”
Section: Brand Personality Of Cultural Tourism Resourcesmentioning
confidence: 99%
“…It comprises five dimensions, namely, sincerity, excitement, competence, sophistication and ruggedness. Although this scale, as noted above, is the most widespread means to measure brand personality (Kumar, 2018), certain authors suggest that its characteristics and dimensions vary from sector to sector (Davies et al, 2018;Ferrandi et al, 2000;Geuens et al, 2009;G omez, 2010;Lara-Rodríguez et al, 2019;Supphellen and Grønhaug, 2003). Of these, sincerity, competence, excitement and sophistication are the dimensions most widely identified when brand personality is applied in different sectors (Davies et al, 2018).…”
Section: Brand Personality Of Cultural Tourism Resourcesmentioning
confidence: 99%
“…For instance, extant research has shown that perceptions of a digital BP increase social media brand engagement (Bernritter et al., 2016), electronic word‐of‐mouth (Torres & Augusto, 2019), and even purchase intentions (Jin & Sung, 2010; Lee & Cho, 2017). Thus, creating and managing a digital BP across digital touchpoints should be a main priority for brand managers (Lara‐Rodríguez et al., 2019). However, digital platforms have morphed and grown in recent years, and yet little is known about the construct of digital BP.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sophistication and ruggedness did not form a strong relationship with the Big Five personality traits (Azoulay and Kapferer, 2003;Geuens et al, 2009). Aaker herself had to report that her model represented the US population only and that different results are expected if used under different circumstances (Aaker, 1997;Lara-Rodríguez et al, 2019;Rup et al, 2021). Wang and Yang (2008) found three major streams of research which had used Aaker's model.…”
Section: Jiabr 124mentioning
confidence: 99%